2020
DOI: 10.1158/1940-6207.capr-19-0538
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Analysis Reveals Adipose–tumor Crosstalk in Patients with Colorectal Cancer

Abstract: ◥Obesity and obesity-driven cancer rates are continuing to rise worldwide. We hypothesize that adipocyte-colonocyte interactions are a key driver of obesity-associated cancers. To understand the clinical relevance of visceral adipose tissue in advancing tumor growth, we analyzed paired tumoradjacent visceral adipose, normal mucosa, and colorectal tumor tissues as well as presurgery blood samples from patients with sporadic colorectal cancer. We report that high peroxisome proliferator-activated receptor gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The pathophysiological state associated with obesity includes visceral adipose tissue and hepatic dysfunction which leads to systemic insulin resistance and inflammation, the dysregulation of adipokines, and dysbiosis (microbial imbalance) (15,16); all of these pathophysiological alterations have been hypothesized to promote a favorable niche for the pathogenesis of CRC (17)(18)(19)(20)(21). Insulin resistant visceral adipose tissue participates in cross-talk with CRC and promotes a favorable niche by secreting metabolites, growth factors, and proinflammatory cytokines (22)(23)(24). Elevated pro-inflammatory cytokines are associated with an increased risk of CRC, (9,(25)(26)(27)(28) and a circulating inflammatory signature (high miR-21, IL-6, and IL-8) predicts lower progressionfree and overall survival of patients with metastatic CRC (29).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological state associated with obesity includes visceral adipose tissue and hepatic dysfunction which leads to systemic insulin resistance and inflammation, the dysregulation of adipokines, and dysbiosis (microbial imbalance) (15,16); all of these pathophysiological alterations have been hypothesized to promote a favorable niche for the pathogenesis of CRC (17)(18)(19)(20)(21). Insulin resistant visceral adipose tissue participates in cross-talk with CRC and promotes a favorable niche by secreting metabolites, growth factors, and proinflammatory cytokines (22)(23)(24). Elevated pro-inflammatory cytokines are associated with an increased risk of CRC, (9,(25)(26)(27)(28) and a circulating inflammatory signature (high miR-21, IL-6, and IL-8) predicts lower progressionfree and overall survival of patients with metastatic CRC (29).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings from Haffa et al have further shed light that BMI poorly reflects fat mass-associated changes in visceral adipose tissue (VAT) [5]. In contrast to subcutaneous adipose tissue (SAT), we and others have demonstrated that excessive visceral adipose tissue (VAT) is more strongly associated with metabolic perturbations and inflammation [5][6][7][8]. Our prior studies also suggest that VAT secretion of fibroblast growth factor-2 (FGF2) is associated with malignant transformation [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…Hydroxyproline is abundant in collagen, and interstitial collagen is a major constituent of the CRC matrix. This may explain the significant change of hydroxyproline observed in CRC patients (Karna et al, 2012 ; Holowatyj et al, 2020 ). Aminolevulinate (also known as 5-aminolevulinic acid or 5ALA) is a precursor to fluorescent protoporphyrin IX.…”
Section: Discussionmentioning
confidence: 98%